COVID-19 in pulmonary critically ill patients: metagenomic identification of fungi and characterization of pathogenic microorganisms - Huang, Changjun; Chang, Siyuan; Ma, Rui; Shang, Yishu; Li, Yuexia; Wang, Yun; Feng, Min; Guo, Wenzhi (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Fungal co-infection is prevalent in critically ill patients with COVID-19. The conventional approach applied to fungal identification has relatively low sensitivity and timeconsuming. The metagenomic Next-Generation Sequencing (mNGS) technology can simultaneously detect a variety of microorganisms, and is increasingly being used for rapid detection and diagnosis of pathogens.In this single center retrospective study, we described the clinical presentation and outcomes of COVID-19 and mNGS positive for fungi in pulmonary critically ill patients during the outbreak of Omicron infection from December 2022 to January 2023.We report fungal positive by mNGS test in 10 of 43 COVID-19 patients with acute respiratory distress syndrome (ARDS) on a single ICU. The number of pathogenic microorganisms detected by mNGS was significantly higher than that by traditional methods, especially in the detection of fungi and viruses. Aspergillus infection was dominant, and most of these patients also had concurrent bacterial or viral infections. Probable or possible COVID-19-associated pulmonary aspergillosis (CAPA) were diagnosed in all 10 patients, and the prognosis was poor.Patients with COVID-19 may be at increased risk of developing fungal infections as well as concurrent bacterial or viral infections, and mNGS can be a powerful tool in identifying these infections. Clinicians should be aware of the increased risk of fungal infections in COVID-19 patients, particularly those who have underlying immunocompromising conditions, and to monitor for early signs of infection.